Pain, obesity, adenosine salvage disruption, and smoking behavior mediate the effect of gut microbiota on sleep disorders: results from network Mendelian randomization and 16S rDNA sequencing - Li, Fu-Jia; Zhang, Ru-Yu; Li, Jin-Yu; Liu, Yu-Ning; Zhang, Zi-Xuan; Du, Li; Li, Yang-Dan-Yu; Liu, Xu; Zhang, Wei; Cui, Gui-Yun; Xu, Chuan-Ying (Frontiers in Microbiology, 2024)
Objectives: To investigate the indirect causalities between the gut microbiota and sleep disorders.Methods: In stage one, we utilized 196 gut microbiota as the exposure factor and conducted a twosample univariable Mendelian randomization (MR) analysis on six sleep disorders, including insomnia, excessive daytime sleepiness (EDS), sleep-wake rhythm disorders (SWRD), obstructive sleep apnea (OSA), and isolated REM sleep behavior disorder (iRBD). In stage two, we validated the MR findings by comparing fecal microbiota abundance between patients and healthy controls through 16S rDNA sequencing. In stage three, we explored indirect pathways by which the microbiota affects sleep, using 205 gut microbiota metabolic pathways and 9 common risk factors for sleep disorders as candidate mediators in a network MR analysis.Results: In stage one, the univariable MR analysis identified 14 microbiota potentially influencing 5 different sleep disorders. In stage two, the results from our observational study validated 4 of these associations. In stage three, network MR analysis revealed the Negativicutes class and Selenomonadales order might worsen insomnia by increasing pain (mediation: 12.43% [95% CI: 0.47%, 24.39%]). Oxalobacter could raise EDS by disrupting adenosine reuptake (25.39% [1.84%, 48.95%]). Allisonella may elevate OSA risk via obesity promotion (36.88% [17.23%, 56.54%]), while the Eubacterium xylanophilum group may lower OSA risk by decreasing smoking behavior (7.70% [0.66%, 14.74%]).Conclusions: Evidence triangulation from the MR and observational study revealed indirect causal relationships between the microbiota and sleep disorders, offering fresh perspectives on how gut microbiota modulate sleep.